Temporal evolution of longitudinal bunch profile in a laser wakefield accelerator - M. Heigoldt; A. Popp; K. Khrennikov; J. Wenz; S. W. Chou; S. Karsch; S. I. Bajlekov; S. M. Hooker; B. Schmidt (Physical Review Special Topics. Accelerators and Beams, 2015)
We present single-shot measurements of the longitudinal bunch profile from a laser-wakefield accelerator with sub-fs resolution, based on detection of coherent transition radiation in a broad spectral range. A previously developed phase retrieval algorithm enables reconstruction of the bunch profile without prior assumptions about its shape. In this study, a variable-length gas target is used to explore the dynamics of bunch evolution. Our results show that once the laser energy is depleted the time structure of the generated electron beam changes from a single bunch to a double bunch structure, well suited for driver-witness type experiments.